Integrated Analysis Reveals the Targets and Mechanisms in Immunosuppressive Effect of Mesalazine on Ulcerative Colitis - Li, Rong; Huang, Xue; Yang, Lu; Liang, Xiao; Huang, Wenjun; Lai, Keng Po; Zhou, Liming (Frontiers in Nutrition, 2022)
Background: Ulcerative colitis (UC) is an inflammatory bowel disease that causes inflammation and ulcers in the digestive tract. Approximately 3 million US adults suffer from this disease. Mesalazine, an anti-inflammatory agent, is commonly used for the treatment of UC. However, some studies have demonstrated side effects of mesalazine, such as acute pancreatitis and hypereosinophilia. Therefore, a better understanding of the anti-inflammatory mechanism of mesalazine in UC could help improve the effectiveness of the drug and reduce its side effects. In this study, we used a dextran sodium sulfate-induced UC mouse model, and applied network pharmacology and omics bioinformatics approaches to uncover the potential pharmaceutical targets and the anti-inflammatory mechanism of mesalazine. Results: Network pharmacology analysis identified the core targets of mesalazine, biological processes, and cell signaling related to immunity and inflammatory responses mediated by mesalazine. Molecular docking analysis then indicated possible binding motifs on the core targets (including TNF-α, PTGS2, IL-1, and EGFR). Metabolomics and 16S metagenomic analyses highlighted the correlation between gut microbiota and metabolite changes caused by mesalazine in the UC model. Conclusions: Collectively, the omics and bioinformatics approaches and the experimental data unveiled the detailed molecular mechanisms of mesalazine in UC treatment, functional regulation of the gut immune system, and reduction of intestinal inflammation. More importantly, the identified core targets could be targeted for the treatment of UC.